Online and Abused: Girls of Color Facing Racialized Sexual Harassment - Pallavi Guha; Paromita Pain (Social Media + Society)
This study, based on 841 surveys with 18-to-19-year-old teenage girls who live, work, or attend school in the Greater Baltimore area, investigated their social media use and the kind of harassment they are subjected to on different platforms. Racialized sexual harassment was rampant, with girls of color being inundated with requests for nudes and sexual comments, especially on Facebook. Participants said that they faced harassment on Instagram irrespective of race, which, as prior studies have shown, has a distinct bias against users of color. Harassment toward girls of color promoted harmful racial stereotypes. American Indians were also deeply impacted. Unrelenting online harassment made participants feel uncomfortable and uneasy (45%), racially discriminated against (40%), and hated (12%) on platforms they chose to socialize and seek information of interest on.